Corporate Culture and Its Connection with External and Internal Public Relations; Kultura korporacyjna i jej zwiazek z zewnetrznymi i wewnetrznymi działaniami public relations - Marcin Kotras (Comparative Economic Research. Central and Eastern Europe, 2010)
The main aim of this article is to present the influence of corporate culture on company's stakeholders. This paper signalises the tendency in corporate communication with its internal and external publics. It is focused on two issues: corporate social responsibility and employer branding. Those two categories are consequences of corporate culture model. – – Głoẃnym celem artykułu jest zaprezentowanie wpływu jaki wywiera charakter kultury korporacyjnej na zwiazanych z przedsiebiorstwem interesariuszy (stakeholders). W artykule zasygnalizowane zostały głoẃne tendencje wyznaczajace charakter komunikacji miedzy organizacja a jej wewnetrznym i zewnetrznym otoczeniem. Tekst koncentruje sie na dwoćh kwestiach: społecznej odpowiedzialnosći przedsiebiorstwa (corporate social responsibilty) i budowanie wizerunku pracodawcy (employer branding), ktoŕe zaprezentowane zostały jako efekty okresĺonego modelu kultury organizacyjnej.
Keywords: 330